Use of a generic protocol in documentation of prescription errors in Estonia, Norway and Sweden - Haavik S; Ekedahl A; Volmer D (Centro de Investigaciones y Publicaciones Farmaceuticas, 2012)
Pharmacists have an important role in detecting, preventing, and solving prescription problems, which if left unresolved, may pose a risk of harming the patient.Objective: The objectives of this study were to evaluate the feasibility of a generic study instrument for documentation of prescription problems requiring contact with prescriber before dispensing. The study was organized: 1) by countries: Estonia, Norway and Sweden; 2) by type of prescriptions: handwritten prescriptions, printouts of prescriptions in the electronic medical record and electronically transmitted prescriptions to pharmacies; and 3) by recording method - self-completion by pharmacists and independent observers.Methods: Observational study with independent observers at community pharmacies in Estonia (n=4) and Sweden (n=7) and self-completed protocols in Norway (n=9).Results: Pharmacists' in Estonia contacted the prescriber for 1.47% of the prescriptions, about 3 times as often as in Norway (0.45%) and Sweden (0.38%). Handwritten prescriptions dominated among the problem prescriptions in Estonia (73.2%), printouts of prescriptions in the electronic medical record (89.1%) in Norway and electronically transmitted prescriptions to pharmacies (55.9%) in Sweden.More administrative errors were identified on handwritten prescriptions and printouts of prescriptions in the electronic medical record in Estonia and in Norway compared with electronically transmitted prescriptions to pharmacies in Sweden (p<0.05 for prescription types and p<0.01 for countries). However, clinically important errors and delivery problems appeared equally often on the different types of prescriptions. In all three countries, only few cases of drug interactions and adverse drug reactions were identified.Conclusion: Despite the different patterns of prescription problems in three countries, the instrument was feasible and can be regarded appropriate to document and classify prescription problems necessitating contact with prescriber before dispensing, irrespective of the type of prescription or recording method.